Investigation of the Proportion of Brucella abortus and Brucella melitensis in Sheep and Goat Milk - Saeid Rostami; Ehsan Rashidian; Amin Jaydari; Heidar Rahimi (Veterinary Medicine International)
Despite the implementation of brucellosis eradication programs in Iran, this disease is still endemic and highly prevalent among ruminants in this country. The infection of small ruminants with Brucella abortus may play a significant role in the continuation of brucellosis among the herds of ruminants. This study investigated the proportion of B. abortus and Brucella melitensis in 150 samples of sheep and goat’s raw milk which were obtained from Lorestan and Hamadan provinces in the western part of Iran using the PCR method. The results revealed that among the Brucella spp. positive samples, 26.5% and 73.4% of the samples were infected with B. abortus and B. melitensis, respectively. The incidence rates of B. abortus among the sheep and goats samples were 6.8% and 12.5%, respectively. There was a significant difference between goats and sheep regarding the proportion of B. abortus. Three samples (2%) (2 goats and one sheep) were simultaneously infected with both B. melitensis and B. abortus. This article renews our knowledge about the causative agent of brucellosis in small ruminants and shows that B. abortus has a relatively high prevalence among those animals in the western regions of Iran, and its role as one of the main factors of abortion among small ruminants should not be ignored. The information provided in the present study is important for the surveillance program, as eradication programs and strategies to prevent the spread of B. abortus among small ruminants that have not been vaccinated against this microorganism may be adapted accordingly.